Horizontal and vertical distributions of atmospheric pressure, 30 to 90 kilometers - Kantor, Arthur J.; Air Force Cambridge Research Laboratories (U.S.)
The distribution with latitude of atmospheric pressure is such that mean monthly pressures generally increase toward the Equator in winter and toward the Pole in summer. The mean maximum January gradient lies between 60 and 40 degrees N, where the pressure changes by roughly one percent of standard per degree of latitude. The height of smallest change is near 85 km. The largest January and July departures from standard occur near 65 km in the arctic where the minimum January value is 65 percent of standard and the maximum in July is 130 percent of standard. A pressure increase near 60 km of more than seven percent per degree of latitude can result from coexistence of cold and warm winter stratospheric thermal regimes within 600 miles over arctic regions. An extreme vertical pressure gradient of 23 percent decrease per km may exist near 85 km for the coldest observed temperature, 130 degree K, at this level. Day-to-day variability of pressure increase with the latitude and altitude to near 65 km. Estimated 2 standard deviations near 65 km reach plus or minus 35 percent during 60 degrees N winter. Theoretical diurnal pressure variations increase with height above 30 km to at least 80 km. (Author). Research supported by the Aerospace Instrumentation Laboratory, Air Force Cambridge Research Laboratories, Office of Aerospace Research, United States Air Force, L.G. Hanscom Field, Bedford, Massachusetts. Aerospace Instrumentation Laboratory Project 8624. AD0635926 (http://www.dtic.mil). "May 1966." Includes bibliographical references (page 13). The distribution with latitude of atmospheric pressure is such that mean monthly pressures generally increase toward the Equator in winter and toward the Pole in summer. The mean maximum January gradient lies between 60 and 40 degrees N, where the pressure changes by roughly one percent of standard per degree of latitude. The height of smallest change is near 85 km. The largest January and July departures from standard occur near 65 km in the arctic where the minimum January value is 65 percent of standard and the maximum in July is 130 percent of standard. A pressure increase near 60 km of more than seven percent per degree of latitude can result from coexistence of cold and warm winter stratospheric thermal regimes within 600 miles over arctic regions. An extreme vertical pressure gradient of 23 percent decrease per km may exist near 85 km for the coldest observed temperature, 130 degree K, at this level. Day-to-day variability of pressure increase with the latitude and altitude to near 65 km. Estimated 2 standard deviations near 65 km reach plus or minus 35 percent during 60 degrees N winter. Theoretical diurnal pressure variations increase with height above 30 km to at least 80 km. (Author). Mode of access: Internet.